Electoral administration, integrity and voting pattern in Nigeria’s 2019 presidential election - Amao, Abdulrazaq Idowu; Ambali, Abdul Rauf (Faculty of Administrative Science and Policy Studies, 2023)
Electoral Administration, Election Integrity and Voting Pattern in the 2019 Presidential Election in Nigeria is not too different from the previous pattern of voting in Nigeria. The aim of this paper is to examine the conduct of 2019 Presidential Election in Nigeria, while also critically examine the salient issues in the 2019 Presidential Election in Nigeria. To suggest/recommend plausible solutions to the problem of electoral integrity in Nigeria. The paper employed secondary source to gather information and used qualitative mode of data analysis. The paper find out that 2019 Presidential Election in Nigeria falls below international standard of electoral integrity. The paper also recommended that international standard practice should be adhere to in order to put Nigeria in her rightful position within/among comity of nations and giants of Africa as she usually claimed. The paper also conclude that for Nigeria to improve her electoral integrity an impartial election management body should be manned by leaders with high personal integrity and their selection process should be devoid of politics.